Alkyl group-decorated g-C3N4 for enhanced gas-phase CO2 photoreduction. Issue 33 (5th August 2022) - Yang, Chao; Hou, Yanting; Luo, Guoqiang; Yu, Jiaguo; Cao, Shaowen
Abstract : Alkyl groups are grafted onto the surface of g-C3 N4 for optimizing the adsorption of reactants and improving the photoelectronic properties, and thus greatly enhance the photocatalytic CO2 reduction activity. Abstract : With excellent physical/chemical stability and feasible synthesis, g-C3 N4 has attracted much attention in the field of photocatalysis. However, its weak photoactivity limits its practical applications. Herein, by easily planting hydrophobic alkyl groups onto g-C3 N4, the hydrophilicity of g-C3 N4 can be well regulated and its specific surface area be enlarged simultaneously. Such a modification ensures enhanced CO2 capture and increased active sites. In addition, the introduction of alkyl groups endows g-C3 N4 with abundant charge density and efficient separation of photoinduced excitons. All these advantages synergistically contribute to the enhanced photocatalytic CO2 reduction performance over the optimized catalyst (DCN90), and the total CO2 conversion is 7.4-fold that of pristine g-C3 N4 (CN).